The impact of breast cancer on fears of exercise and exercise identity. Issue 7 (July 2022) - Murray, James; Perry, Rebecca; Pontifex, Emma; Selva-Nayagam, Sudarsha; Bezak, Eva; Bennett, Hunter
Abstract: Objectives: Low exercise adherence is common amongst breast cancer (BC) patients. This study aimed to understand BC patients exercise identity and fears of exercise to identify barriers to exercise participation. Methods: Women (18 years plus) currently undergoing, or completed (in remission), chemotherapy for BC, and women (18 years plus) with no cancer history completed three validated questionnaires: Exercise Identity Scale (EI), Exercise Fear Avoidance Scale (EFAS) and Fear of Physical Activity/Exercise Scale – Breast Cancer. Results: 86 women were included (BC: n = 51 – non-cancer: n = 35). There were no significant differences between groups when comparing overall EI (p = 0.240; d =0.127) and EFAS (p = 0.060; d =0.203) scores. BC reported significantly higher scores on specific questions related to fear during exercise (EFAS 2, 3, and 5; p = <0.005). Associations were observed between EI and EFAS questionnaire scores in BC (r = −0.342; p = 0.014), and EI scores and exercise levels in both groups (BC, r = 0.527; p = <0.001; non-cancer, r = 0.639; p = <0.001). Conclusion: Results suggest women with BC may have specific concerns and fears of exercise compared to age-matched controls. Education may mitigate fears, increase exercise identity, and promote exercise uptake. Practical implications: Education provided by clinicians at BC diagnosis regarding the benefits and safety of exercise may help mitigate fear and promote exercise identity. Highlights: Women with breast cancer experience unique fears around exercise engagement. Exercise identity was negatively associated with fear in women with breast cancer. Exercise identity was positively associated with current exercise levels. Education provided by clinicians may mitigate fear and promote exercise identity.